Conversations on Art-Science Collaboration and Vaccine Hesitancy (Imaginations: Journal of Cross-Cultural Image Studies, 2020)
Kaisu Koski, a Finnish artist-researcher based in the UK and the Netherlands, and Johan Holst, a leading vaccinologist in Norway, discuss their collaborative work exploring vaccine hesitancy in parents. The collaboration was initiated as part of Koski’s ongoing research in creating films for medical education. Together, the authors developed collaborative exchanges on vaccine-critical parents’ health beliefs and visualized them in a multimodal artwork series. Due to the authors’ different viewpoints on vaccines, this project raises questions about positionality in interdisciplinary research and the power of visualization in health communication.
Keywords: vaccine hesitancy; health communication; health beliefs; visualization; art-science collaboration